PENDIDIKAN MULTIKULTURAL DI MADRASAH PEMBANGUNAN CIPUTAT TANGERANG - Muhamad Murtadlo (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2014)
Implementation of multicultural education in madrasas is a very interesting topic to present in this paper, considering the characteristics of learners which can be said to be more homogeneous than the secular schools. In general, the multicultural education has become necessary to be applied in educational institutions with heterogeneous learners, especially in terms of their beliefs. Multicultural values taught in school will be more easily practiced in the social life among such heterogeneous students. But this is not the case with homogenous madrasas. The development of multicultural values in madrasahs will call for its own concepts and strategies.Using a qualitative research approach with in-depth interviews as the main data collection instrument, this paper tries to formulate multicultural education conducted by the Madrasah Pembangunan, Ciputat, Tangerang, by seeing how the context, concept, and its implementation in educational systems are organized. The findings include, among others, the facts that multicultural education in madrasah is nothing new because multicultural values have been taught in many subjects there. These multicultural values are developed and introduced and required by the students in Madrasah Pembangunan to deal with heterogeneous members of society such as the values of tolerance, empathy, cooperation; and four main properties of Muhammad Rasululllah (Genuine, Trustworthy, Authentic, Intelligent). Other values include confi dence, quality work and competitive.